Decreased Long‐Term Severe Acute Respiratory Syndrome Coronavirus 2–Specific Humoral Immunity in Liver Transplantation Recipients 12 Months After Coronavirus Disease 2019. Issue 6 (17th January 2022) - Caballero‐Marcos, Aránzazu; Citores, María Jesús; Alonso‐Fernández, Roberto; Rodríguez‐Perálvarez, Manuel; Valerio, Maricela; Graus Morales, Javier; Cuervas‐Mons, Valentín; Cachero, Alba; Loinaz‐Segurola, Carmelo; Iñarrairaegui, Mercedes; Castells, Lluís; Pascual, Sonia; et al.
Abstract : Long‐term humoral immunity and its protective role in liver transplantation (LT) patients have not been elucidated. We performed a prospective multicenter study to assess the persistence of immunoglobulin G (IgG) antibodies in LT recipients 12 months after coronavirus disease 2019 (COVID‐19). A total of 65 LT recipients were matched with 65 nontransplanted patients by a propensity score including variables with recognized impact on COVID‐19. LT recipients showed a lower prevalence of anti‐nucleocapsid (27.7% versus 49.2%; P = 0.02) and anti‐spike IgG antibodies (88.2% versus 100.0%; P = 0.02) at 12 months. Lower index values of anti‐nucleocapsid IgG antibodies were also observed in transplantation patients 1 year after COVID‐19 (median, 0.49 [interquartile range, 0.15‐1.40] versus 1.36 [interquartile range, 0.53‐2.91]; P < 0.001). Vaccinated LT recipients showed higher antibody levels compared with unvaccinated patients ( P < 0.001); antibody levels reached after vaccination were comparable to those observed in nontransplanted individuals ( P = 0.70). In LT patients, a longer interval since transplantation (odds ratio, 1.10; 95% confidence interval, 1.01‐1.20) was independently associated with persistence of anti‐nucleocapsid IgG antibodies 1 year after infection. In conclusion, compared with nontransplanted patients, LT recipients show a lower long‐term persistence of anti–severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) antibodies. However, SARS‐CoV‐2 vaccination after COVID‐19 in LT patients achieves a significant increase in antibody levels, comparable to that of nontransplanted patients.